METODE ALFATIH: SEBUAH INOVASI DALAM PEMBELAJARAN KITAB KUNING DI PONDOK PESANTREN - Ruslan; Hotibatul Ummah (ANDRAGOGI, 2022)
The existence of an Islamic boarding school cannot be separated from learning the yellow book. However, learning the yellow book often leaves problems. This paper aims to describe : 1) the implementation of learning the yellow book through the Alfatih method at the Sumber Mas Islamic Boarding School, Almadinah Region, West Rombiya Village, Ganding District, Sumenep Regency along with the advantages and disadvantages of the Alfatih method. This study uses a qualitative research approach with a type of case study. Data collection techniques were carried out using interviews, observation, and documentation. The data analysis technique is done by three stages, namely data condensation, data display, and drawing conclusions/verification. The research findings show that: 1) the implementation of learning the yellow book through the Alfatih method at the Sumber Mas Islamic Boarding School, Almadinah Region, Ganding District, Sumenep Regency is carried out in 3 (three) stages, namely the initial stage, the core stage, and the final stage; 2) the advantages of the Alfatih method in learning the yellow book include the use of MLT, can be applied optimally and can be minimal, no need to memorize definitions, not complicated Nahwu and Sharraf, simple in various aspects, accustomed to reading the yellow book. While the shortcomings of the Alfatih method are that they are not used to writing and the book is incomplete.